Pengalaman Guru Dalam Menghadapi Tantangan Pembelajaran Daring : (Studi Kasus Di SMP Negeri 1 Kabupaten Deli Serdang) - Zalukhu, Ade Rostian; Shabrina, Fathiyyah; Siregar, Pani Akhiruddin (EL-EMIR Institute, 2025)
The Covid-19 pandemic has forced the education sector to shift abruptly to online learning. This sudden transition presented various challenges, particularly for teachers who had to quickly adapt to digital technologies while ensuring that the learning process remained effective. This study aims to explore the experiences of teachers in facing the challenges of online learning at a public junior high school 1 District Deli Serdang. A qualitative method with a case study approach was used. Data were collected through interviews and observations with five teachers from different subject areas. The results reveal that teachers encountered several obstacles, including limited access to technology infrastructure, low student motivation, and a lack of initial competence in using online learning platforms. Despite these difficulties, teachers demonstrated resilience and creativity by implementing adaptive teaching strategies such as creating simple instructional videos, using a personal approach with students, and collaborating with parents. These findings reinforce the importance of institutional support and technological training for teachers. The study concludes that although the challenges were significant, teachers were able to adapt effectively, and their strategies can serve as valuable references for improving the quality of future online learning practices.